Impact of Strategic Planning and Innovation on Organisational Performance of the Saudi Red Crescent Authority - Alotaibi, Hana J M (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
A survey-based empirical examination was made on the impact of strategic planning and innovation on the organisational performance of Saudi Red Crescent Authority. Data was collected from 212 workers in Riyadh and Jeddah. The majority of the sample are educated and experienced. The results of a multiple regression analysis test revealed statistically significant positive associations between each of strategic planning and innovation with organisational performance. Theoretical and practical implications are drawn and recommendations are made as well to assist decision-makers in undertaking strategic planning and emphasising innovation.